Composite material, application product thereof and manufacturing method of composite material
By combining multi -hydroxyl groups and at least 1hl -based polydamine with substrates, and reducing the number of hydroxyl groups through a hydroxyl group through a hydroxyl response, the angle of the substrate dielectric loss is too high, and the corner consumption of the dielectric loss and the consumption of the angle of the dielectric loss and the cutting angle consumption and the cutting angle and the consumption of the corner and the cutting angle consumption and the cutting angle of the dielectric loss. Improve the effect of wiring board heat dissipation, suitable for electronic devices in 5G communication systems.
Patent Information
- Application Number
- CN202380046154.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-06-05
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to effectively reduce the dielectric loss tangent of the substrate, especially in high frequency bands, which depend on the orientation polarization of organic molecules in the substrate material, resulting in an increase in transmission loss.
Polydopamine containing multiple hydroxyl groups and at least 1 acyl group is used to combine with the substrate, and the number of hydroxyl groups in the polydopamine is reduced through an acylation reaction, thereby reducing the dielectric loss tangent.
By reducing the dielectric loss tangent of the base material, the transmission loss of high-frequency signals is reduced, and the heat dissipation and thermal conductivity of the wiring board are improved. It is suitable for electronic equipment in 5G communication systems.
Smart Images

Figure CN119365536A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a composite material, a product using the composite material, and a method for manufacturing the composite material. Background Art
[0002] In recent years, the performance requirements for electronic devices have increased with the expansion of the fifth-generation mobile communication system (5G) in the electronics field. For example, 5G uses higher frequency bands to achieve faster communication speeds than previous generations. Therefore, electronic devices require wiring boards that support high frequencies.
[0003] The transmission loss of the transmission line of the wiring board depends on the frequency. The higher the frequency of the signal, the greater the transmission loss. The transmission loss depends on the relative dielectric constant and the dielectric loss tangent. Therefore, in order to reduce the transmission loss of high-frequency signals, the substrate material constituting the insulating layer of the wiring board is required to have a low relative dielectric constant and a low dielectric loss tangent. Especially in high frequency bands, the dielectric loss tangent greatly depends on the orientation polarization of the organic molecules contained in the substrate material. Therefore, it is necessary to reduce the polar groups such as hydroxyl and amino groups contained in the substrate material.
[0004] In addition, since large-capacity communications such as 5G use high-frequency bands, the transmission distance of radio waves is short. Therefore, it is necessary to increase the output power of electronic equipment. In addition, with the realization of high integration and miniaturization, the installation density of circuits has also increased. In order to meet these needs, the heat generation per unit area of the wiring board will increase. Therefore, the wiring board is required to have high heat dissipation. In order to improve the heat dissipation of the wiring board, there is a scheme to make the substrate material of the insulating layer constituting the wiring board contain a filler (filler) with excellent thermal conductivity to improve the thermal conductivity of the wiring board.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2018-043899
[0008] Non-patent literature
[0009] Non-Patent Document 1: Haeshin Lee, Shara M. Dellatore, William M. Miller, Phillip B. Messersmith, Science, 2007, vol. 318, 426-430
[0010] Non-patent literature 2: Heng Shen, Jing Guo, Hao Wang, Ning Zhao, Jian Xu, ACS Appl. Mater. Interfaces, 2015, 7, 5701-5708 Summary of the Invention
[0011] Problems to be solved by the invention
[0012] In the prior art, it is desirable to reduce the dielectric loss tangent of a substrate.
[0013] Means used to solve problems
[0014] The composite material disclosed herein has:
[0015] substrate, and
[0016] Polydopamine containing multiple hydroxyl groups and at least one acyl group.
[0017] Effects of the Invention
[0018] According to the present disclosure, the dielectric loss tangent of the substrate can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a diagram showing a schematic configuration of a composite material according to the first embodiment.
[0020] Figure 2A This is a diagram illustrating the behavior of an acylating agent when the acylating agent is added to a substrate to which polydopamine is adhered in a hydrophobic solvent.
[0021] Figure 2B This is a diagram illustrating the behavior of an acylating agent when the acylating agent is added to a substrate to which polydopamine is adhered in a hydrophilic solvent.
[0022] Figure 3 This is a flowchart showing an example of a method for producing a composite material according to the first embodiment.
[0023] Figure 4 This is a diagram showing a schematic configuration of a resin composition according to a fourth embodiment.
[0024] Figure 5 This is a cross-sectional view of a film with resin according to a sixth embodiment.
[0025] Figure 6 This is a cross-sectional view of the metal foil with resin according to the seventh embodiment.
[0026] Figure 7 This is a cross-sectional view of a metal-clad laminate according to the eighth embodiment.
[0027] Figure 8 This is a cross-sectional view of a wiring board according to a ninth embodiment. DETAILED DESCRIPTION
[0028] (Understanding that forms the basis of this disclosure)
[0029] Increasing the filler content in a resin composition to improve the heat dissipation of a wiring board can impair mechanical properties such as flexibility, and the insulating layer can become brittle. This is believed to be due to filler aggregation within the resin composition. Chemical modification of the filler surface is effective in suppressing filler aggregation and improving dispersibility.
[0030] Boron nitride is a material with high thermal conductivity, excellent heat dissipation, and excellent electrical insulation. Therefore, in recent years, boron nitride has been paid attention to as the filler of the insulating layer of wiring board (such as patent documentation 1). However, the amount of the functional group existing on the surface of the particles of boron nitride is few, and the major part of its surface is inactive. Therefore, it is difficult to directly process the surface of the particles of boron nitride by methods such as silane coupling to improve the dispersibility of the particles in the resin combination.
[0031] Here, the dopamine-containing protein secreted by the foot gland of the blue mussel (Mytilus galloprovincialis), a species of bivalve, exhibits stable adhesive strength even in seawater and is known as a natural adhesive. According to Non-Patent Document 1, immersing a substrate in an aqueous dopamine solution forms a thin film of polydopamine on the surface of the substrate through auto-oxidative polymerization of the dopamine. Non-Patent Document 2 describes utilizing this property to coat boron nitride with polydopamine, thereby improving the dispersibility of boron nitride as a filler.
[0032] However, polydopamine has a large amount of hydroxyl groups and therefore has the property of easily absorbing moisture in the atmosphere, i.e., hydrophilicity. Therefore, when using boron nitride attached with polydopamine as a filler, first, there is a risk of dielectric loss tangent deterioration caused by hydroxyl groups and adsorbed water. Second, sometimes, due to the heating in the solder reflow process, the water adsorbed on the surface of the polydopamine is evaporated, which can produce bubbles. There is also a risk of various unfavorable conditions caused by the accumulation of these bubbles inside the wiring board.
[0033] The present inventors conducted extensive research on reducing the dielectric loss tangent of a substrate, and as a result, came up with the composite material disclosed herein.
[0034] (Summary of one aspect of the present disclosure)
[0035] The composite material according to the first aspect of the present disclosure comprises:
[0036] substrate, and
[0037] Polydopamine containing multiple hydroxyl groups and at least one acyl group.
[0038] According to the above configuration, the dielectric loss tangent of the composite material can be reduced.
[0039] In the second aspect of the present disclosure, for example, in the composite material of the first aspect, the at least one acyl group may be generated by acylation of at least a part of the plurality of hydroxyl groups.
[0040] In the third embodiment of the present disclosure, for example, the composite material of the first embodiment can satisfy 0.20 ≤ N2 / N1, where the number of moles of the plurality of hydroxyl groups contained in the polydopamine is defined as N1 and the number of moles of the at least one acyl group contained in the polydopamine is defined as N2. With this configuration, the dielectric loss tangent of the composite material can be further reduced.
[0041] In the fourth aspect of the present disclosure, for example, the composite material of the third aspect can satisfy 0.30≤N2 / N1. According to the above configuration, the dielectric loss tangent of the composite material can be further reduced.
[0042] In the fifth aspect of the present disclosure, for example, the composite material of the third or fourth aspect may satisfy N2 / N1≤0.5.
[0043] In the sixth aspect of the present disclosure, for example, in the composite material of any of the first to fifth aspects, the substrate may comprise at least one member selected from the group consisting of boron nitride, aluminum nitride, silicon nitride, aluminum oxide, magnesium oxide, and silicon dioxide. The composite material of the present disclosure is particularly useful when the substrate comprises at least one member selected from the foregoing group.
[0044] In the seventh aspect of the present disclosure, for example, in the composite material of the sixth aspect, the substrate may include boron nitride. The composite material of the present disclosure is particularly useful when the substrate includes boron nitride.
[0045] The composite material according to the eighth aspect of the present disclosure comprises:
[0046] substrate, and
[0047] Polydopamine comprising a functional group represented by -OCOR,
[0048] R is a hydrocarbon group.
[0049] The filler according to the ninth aspect of the present disclosure includes the composite material according to any one of the first to eighth aspects. According to the above configuration, the dielectric loss tangent of the filler can be reduced.
[0050] The resin composition of the tenth aspect of the present disclosure contains the filler of the ninth aspect. According to the tenth aspect, a resin composition having a low dielectric loss tangent and excellent heat resistance can be provided.
[0051] The prepreg according to the eleventh aspect of the present disclosure comprises the resin composition according to the tenth aspect or a semi-cured product of the resin composition.
[0052] The resin-coated film according to the twelfth aspect of the present disclosure includes:
[0053] A resin layer comprising the resin composition of the tenth embodiment or a semi-cured product of the resin composition, and
[0054] Support film.
[0055] The resin-coated metal foil according to the thirteenth aspect of the present disclosure includes:
[0056] A resin layer comprising the resin composition of the tenth embodiment or a semi-cured product of the resin composition, and
[0057] Metal foil.
[0058] A metal-clad laminate according to a fourteenth aspect of the present disclosure includes:
[0059] An insulating layer comprising a cured product of the resin composition of the tenth embodiment or a cured product of the prepreg of the eleventh embodiment, and
[0060] Metal foil.
[0061] A wiring board according to a fifteenth aspect of the present disclosure includes:
[0062] An insulating layer comprising a cured product of the resin composition of the tenth embodiment or a cured product of the prepreg of the eleventh embodiment, and
[0063] wiring.
[0064] According to the 11th to 15th aspects, various application products suitable for high frequencies can be provided.
[0065] The method for producing a composite material according to the sixteenth aspect of the present disclosure includes the following steps:
[0066] contacting a material comprising polydopamine containing a plurality of hydroxyl groups with an acylating agent, and
[0067] Acylate at least a portion of the plurality of hydroxyl groups,
[0068] The material includes a substrate and the polydopamine attached to the surface of the substrate.
[0069] According to the above configuration, a composite material having a reduced dielectric loss tangent can be produced.
[0070] In the seventeenth aspect of the present disclosure, for example, in the method for producing a composite material according to the sixteenth aspect, the acylation may be performed in a hydrophilic solvent. According to the above configuration, the dielectric loss tangent of the composite material is further reduced.
[0071] In the eighteenth aspect of the present disclosure, for example, in the method for producing a composite material according to the seventeenth aspect, the hydrophilic solvent may contain water. According to the above configuration, the dielectric loss tangent of the composite material is further reduced.
[0072] In the 19th aspect of the present disclosure, for example, in the method for producing a composite material according to any one of the 16th to 18th aspects, the acylating agent may include an acid anhydride. According to the above configuration, the dielectric loss tangent of the composite material is further reduced.
[0073] In the 20th aspect of the present disclosure, for example, in the method for producing a composite material according to the 19th aspect, the acid anhydride may include at least one selected from the group consisting of methacrylic anhydride, acrylic anhydride, acetic anhydride, and benzoic anhydride. With this configuration, the dielectric loss tangent of the composite material is further reduced.
[0074] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0075] (Implementation 1)
[0076] Below, use Figures 1 to 3 Implementation 1 will be described.
[0077] [Composite Materials]
[0078] Figure 1 1 is a diagram showing a schematic configuration of a composite material 10 according to Embodiment 1. The composite material 10 includes a substrate 1 and polydopamine 2. At least a portion of the hydroxyl groups included in the polydopamine 2 is acylated.
[0079] Polydopamine 2 can be attached to the surface of substrate 1. Specifically, polydopamine 2 can be attached to the surface of substrate 1 by chemically modifying the surface of substrate 1 with polydopamine 2. Polydopamine 2 can cover at least a portion of the surface of substrate 1. Polydopamine 2 can cover the entire surface of substrate 1 or only a portion of the surface of substrate 1.
[0080] When a compound having hydroxyl groups, such as polydopamine, reacts with an acylating agent in the presence of a catalyst, the hydroxyl groups are acylated. In composite material 10, at least a portion of the hydroxyl groups contained in polydopamine 2 are acylated. In other words, the amount of hydroxyl groups contained in polydopamine 2 is reduced in composite material 10. Therefore, composite material 10 can achieve a reduced dielectric loss tangent.
[0081] In the composite material 10, whether at least a portion of the hydroxyl groups contained in the polydopamine 2 are acylated can be confirmed, for example, by analyzing the infrared absorption spectrum of the composite material 10. Specifically, in the infrared absorption spectrum, the acylation can be confirmed by absorption due to the stretching vibration of the carbonyl group contained in the acylating agent used for acylation. The infrared absorption spectrum is a spectrum obtained by the diffuse reflectance method of Fourier transform infrared spectroscopy (FT-IR).
[0082] The number of moles of hydroxyl groups contained in polydopamine 2 is defined as N1, and the number of moles of acyl groups contained in polydopamine 2 is defined as N2. In this case, the composite material 10 may satisfy 0.20≤N2 / N1.
[0083] The number of moles of acyl groups N2 contained in polydopamine 2 reflects the number of moles of acyl groups derived from the acylating agent contained in polydopamine 2. Therefore, the value calculated from N2 / N1 indicates the extent to which the acylating agent reacted with the hydroxyl groups contained in polydopamine 2, i.e., the acylation rate. In this embodiment, since 0.20 ≤ N2 / N1 is satisfied, the acylating agent reacted sufficiently with the hydroxyl groups contained in polydopamine 2. Consequently, composite material 10 achieves a reduced dielectric loss tangent.
[0084] The number of moles N1 is calculated based on the following formula (1).
[0085] N1=(W P / X D )×2 formula (1)
[0086] In the above formula (1), W P is the mass (g) of polydopamine 2 attached to substrate 1. D is the molar mass (g / mol) of the dopamine monomer, which is 147.1 (g / mol). The value 2 in the above formula (1) is the number of hydroxyl groups contained in the dopamine monomer.
[0087] The number of moles N2 is calculated based on the following formula (2).
[0088] N2=W A / X A Equation (2)
[0089] In the above formula (2), W A is the mass (g) of the acylating agent contained in polydopamine 2. A is the molar mass (g / mol) of the acyl group, specifically, the molar mass (g / mol) of the RCO portion in the acylating agent represented by (RCO)2O.
[0090] W P and W AFor example, it can be calculated by thermogravimetric analysis (TGA) under the following conditions: The mass M1 (g) of the substrate 1 before the polydopamine 2 is attached, and the mass M2 (g) of the substrate 1 after the polydopamine 2 is attached are measured. The mass W of the polydopamine 2 attached to the substrate 1 can be calculated based on the difference between the measured values. P The mass M2 (g) of the substrate 1 to which polydopamine 2 is attached before acylation of polydopamine 2 and the mass M3 (g) of the composite material 10 after acylation of polydopamine 2 are measured. The mass W of the acylating agent contained in polydopamine 2 can be calculated from the difference between the measured values. A .
[0091] <Condition>
[0092] ·Measurement starting temperature: 20℃
[0093] Heating rate: 5℃ / min
[0094] Heating temperature: 800℃
[0095] ·Measurement atmosphere: Atmosphere
[0096] ·Gas flow rate of measurement atmosphere: 200mL / min
[0097] Note that polydopamine 2 is soluble in an alkaline solution. Therefore, by immersing the substrate 1 to which polydopamine 2 has been attached in, for example, a NaOH solution, the polydopamine 2 can be removed from the substrate 1 to obtain the original substrate 1.
[0098] The composite material 10 can satisfy 0.30≤N2 / N1. According to the above configuration, the dielectric loss tangent of the composite material 10 can be further reduced.
[0099] The composite material 10 can satisfy N2 / N1≤0.5. According to the above configuration, the dielectric loss tangent of the composite material 10 is further reduced.
[0100] (Acylating Agent)
[0101] Acylation is carried out using an acylating agent. The acylating agent is not particularly limited as long as it can react with polar functional groups such as hydroxyl groups contained in polydopamine 2 to acylate them. The acylating agent may be an acid anhydride. As well-known acylating agents, for example, carboxylic anhydrides can be listed. More specifically, methacrylic anhydride, acetic anhydride, benzoic anhydride, propionic anhydride, etc. can be listed. The acid anhydride may contain at least one selected from the group consisting of methacrylic anhydride, acrylic anhydride, acetic anhydride and benzoic anhydride. In the case where the acylating agent has a double bond at the end, the double bond reacts with the reactive residue of the resin in the insulating layer to form a bond, thereby improving the adhesion between the composite material 10 and the resin. From this point of view, the acylating agent is particularly preferably methacrylic anhydride or acetic anhydride.
[0102] (Solvent)
[0103] Acylation can be performed by adding an acylating agent to a solvent. As the solvent, either a hydrophilic solvent or a hydrophobic solvent can be used. In the present disclosure, a hydrophilic solvent refers to a solvent with a high affinity for water, and examples thereof include solvents having hydroxyl groups. A hydrophobic solvent refers to a solvent with a low affinity for water, and examples thereof include solvents without hydroxyl groups.
[0104] The solvent may be a hydrophilic solvent. That is, acylation can be performed by adding an acylating agent to a hydrophilic solvent. Polydopamine 2 exhibits hydrophilicity and therefore tends to swell in hydrophilic solvents. Therefore, the use of a hydrophilic solvent can promote the intrusion of the acylating agent into the interior of the polydopamine 2 film. This improves the acylation rate of polydopamine 2.
[0105] Figure 2A and Figure 2B This is a diagram illustrating the behavior of the acylating agent 3 when the acylating agent 3 is added to the substrate 11 to which the polydopamine 21 is attached. Figure 2A An example is shown in which the hydrophobic solvent 4 is used as the solvent. Figure 2B An example of the case where a hydrophilic solvent 5 is used as a solvent is shown. Figure 2A and Figure 2B As shown in FIG, when the acylating agent 3 is added to the substrate 11 to which the polydopamine 21 is attached, at least a portion of the hydroxyl groups contained in the polydopamine 21 is acylated. As a result, the amount of hydroxyl groups contained in the polydopamine 21 is reduced, thereby achieving a reduction in the dielectric loss tangent. However, as Figure 2A As shown in FIG. 1 , when a hydrophobic solvent 4 is used as a solvent, there is a tendency that the surface of the polydopamine 21 film is acylated, but the penetration of the acylating agent into the interior of the polydopamine 21 film is suppressed. This is because polydopamine 21 is hydrophilic, and thus the polydopamine 21 film tends to shrink in the hydrophobic solvent 4. On the other hand, Figure 2B As shown, the thin film of polydopamine 21 tends to swell in the hydrophilic solvent 5. Therefore, when the hydrophilic solvent 5 is used as the solvent, the acylating agent 3 is promoted to penetrate into the interior of the thin film of polydopamine 21. This can not only reduce the hydroxyl groups present on the surface of the thin film of polydopamine 21, but also fully reduce the hydroxyl groups present in the interior of the thin film of polydopamine 21.
[0106] The hydrophilic solvent is not particularly limited. Examples of the hydrophilic solvent include various alcohols such as water, methanol, isopropanol, dimethyl sulfoxide (DMSO), ethanol, butanol, and propanol. These hydrophilic organic solvents can be used alone or in combination of two or more. Water is particularly preferred as the hydrophilic solvent. If the hydrophilic solvent is water, the acylating agent can be fully infiltrated into the interior of the film of polydopamine 2.
[0107] [Base material]
[0108] The substrate 1 may include at least one selected from the group consisting of boron nitride, aluminum nitride, silicon nitride, aluminum oxide, magnesium oxide, and silicon dioxide. The composite material 10 is particularly useful when the substrate 1 includes at least one selected from the above group.
[0109] The substrate 1 may include boron nitride. The composite material 10 is particularly useful when the substrate 1 includes boron nitride. Boron nitride is also used, for example, as a filler due to its excellent thermal conductivity. The substrate 1 may include boron nitride.
[0110] As boron nitride, hexagonal boron nitride (h-BN) with a graphite-type layered structure, diamond-type cubic boron nitride (c-BN), and amorphous boron nitride (a-BN) can be used. h-BN is particularly useful because it can be easily synthesized and has excellent thermal conductivity, electrical insulation, chemical stability, and heat resistance. As boron nitride, boron nitride particles can be used. Boron nitride particles are generally white. The shape of the boron nitride particles is not particularly limited. The shape of the boron nitride particles can be, for example, scaly, spherical, ellipsoidal, rod-shaped, etc.
[0111] The average particle size of the boron nitride particles is not particularly limited. The average particle size of the boron nitride particles can be, for example, 0.05 μm or more and 100 μm or less, or 0.1 μm or more and 50 μm or less. In the present disclosure, the average particle size of the boron nitride particles refers to the median particle size. The median particle size refers to the particle size (d50) at which the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution is measured, for example, using a laser diffraction measuring device.
[0112] [Polydopamine]
[0113] Polydopamine 2 is a dopamine polymer, and may have, for example, one or both of the two repeating units represented by the following formula (1): In the following formula (1), the indoline skeleton may be an indole skeleton.
[0114] [Chemical Formula 1]
[0115]
[0116] In the above formula (1), n is an integer greater than or equal to 1. In the above formula (1), n may be an integer greater than or equal to 2.
[0117] The polydopamine 2 may be in the form of a thin film on the surface of the substrate 1. The thickness of the polydopamine 2 thin film is, for example, 1 nm to 300 nm. The polydopamine 2 thin film covers at least a portion of the surface of the substrate 1. The polydopamine 2 thin film may also be as follows: Figure 1 As an example, the entire surface of the substrate 1 is covered.
[0118] The adhesion of polydopamine 2 to the substrate 1 can be confirmed by the surface of the substrate 1 being colored dark brown.
[0119] In this specification, even if some of the functional groups derived from dopamine in a polymer are altered due to binding to other substances, the polymer will be referred to as "polydopamine." An example of a functional group change is the loss of a hydroxyl group resulting from the replacement of a hydroxyl group in polydopamine with an acyl group from another substance. It should be noted that this replacement is a typical example of the chemical reaction based on the aforementioned acylation.
[0120] [Method for producing composite materials]
[0121] Next, a method for producing the composite material 10 will be described.
[0122] Figure 3 1 is a flowchart illustrating an example of a method for producing a composite material 10. The method for producing the composite material 10 includes the steps of contacting a material containing polydopamine 2 with an acylating agent (step S1), and acylating at least a portion of the hydroxyl groups contained in the polydopamine 2 (step S2). The material containing polydopamine 2 includes a substrate 1 and polydopamine 2 attached to the surface of the substrate 1.
[0123] The material containing polydopamine 2 can be obtained by utilizing the auto-oxidative polymerization of dopamine to attach polydopamine 2 to the surface of substrate 1. Specifically, by contacting a dopamine solution with substrate 1 and oxidatively polymerizing dopamine, polydopamine 2 can be attached to the surface of substrate 1 to form a thin film of polydopamine 2.
[0124] A dopamine solution can be obtained by adding dopamine hydrochloride to a Tris-HCl solution adjusted to pH 8.5 and stirring. The concentration of the dopamine solution is not particularly limited, and is, for example, in the range of 0.01 mg / mL to 30 mg / mL. The pH of the dopamine solution is in the range of pH 6 to pH 11, and can be in the range of pH 8 to pH 10. The pH of the dopamine solution can be adjusted by mixing a Tris-HCl solution or the like. The temperature of the dopamine solution during oxidative polymerization is, for example, 10° C. to 100° C. The polymerization time is, for example, 1 hour to 48 hours. The thickness of the thin film of polydopamine 2 is, for example, 1 nm to 300 nm. The thickness of the thin film of polydopamine 2 can be controlled by the polymerization time.
[0125] In step S1, a material containing polydopamine 2 is contacted with an acylating agent. Examples of the acylating agent are as described above.
[0126] In step S2, with respect to the material containing polydopamine 2, at least a portion of the hydroxyl groups contained in the polydopamine 2 is acylated. In this way, the composite material 10 can be obtained.
[0127] Acylation can be carried out by adding an acylating agent to a hydrophilic solvent. Examples of the hydrophilic solvent are as described above. Water is particularly preferred as the hydrophilic solvent.
[0128] like Figure 2B As shown, the thin film of polydopamine 21 tends to swell in the hydrophilic solvent 5. Therefore, when the hydrophilic solvent 5 is used as the solvent, the acylating agent 3 is promoted to penetrate into the interior of the thin film of polydopamine 21. This can not only reduce the hydroxyl groups present on the surface of the thin film of polydopamine 21, but also fully reduce the hydroxyl groups present in the interior of the thin film of polydopamine 21.
[0129] The acylation reaction can be carried out in the presence of a catalyst. Examples of the catalyst include DMAP (N,N-dimethylaminopyridine) and aluminum chloride. For example, the acylation reaction proceeds as shown in the following mechanism diagram. The following mechanism diagram illustrates an example using a carboxylic anhydride as the acylating agent. The hydroxyl groups of polydopamine 2 react with the acylating agent in the presence of a catalyst (DMAP). This acylates the hydroxyl groups of polydopamine 2.
[0130] [Chemical Formula 2]
[0131]
[0132] The reaction temperature and reaction time for acylation are appropriately selected according to the amount of catalyst and acylating agent. The reaction temperature is usually above 0°C and below 100°C, can be above 5°C and below 50°C, or can be above 10°C and below 30°C. The reaction time is usually above 1 hour and below 48 hours, can be above 5 hours and below 40 hours, or can be above 10 hours and below 30 hours. If the reaction time is more than 5 hours, acylation is fully carried out, so the hydroxyl groups contained in polydopamine can be fully reduced. If the reaction time is less than 40 hours, the reduction in productivity and the increase in cost can be suppressed.
[0133] In the high-frequency range from GHz to THz, the dielectric loss tangent greatly depends on the orientation polarization of the organic molecules contained in the wiring board material. The hydroxyl groups in polydopamine 2 can increase the dielectric loss tangent. However, in composite material 10, since the number of hydroxyl groups in polydopamine 2 is reduced through acylation, the dielectric loss tangent of composite material 10 can be reduced.
[0134] (Implementation Method 2)
[0135] The heat dissipation gap filler of the present embodiment includes the composite material 10 of the first embodiment.
[0136] In this disclosure, a heat dissipation gap filler is a filler used to fill air pockets or gaps in electronic components, such as substrate materials, by applying it to them, thereby dissipating heat from the components. This gap filler is a curable heat dissipation paste that solidifies from a paste into a sheet. The heat dissipation gap filler of this embodiment can improve the filler's heat resistance and inhibit moisture adsorption into the filler.
[0137] The heat dissipation gap filler of the present embodiment can be produced by kneading the composite material 10 of the first embodiment with an epoxy resin, a silicone resin, or a non-silicone acrylic resin or a ceramic resin, for example.
[0138] (Implementation 3)
[0139] The filler for heat-dissipating grease according to the present embodiment includes the composite material 10 according to the first embodiment.
[0140] In this disclosure, the term "heat dissipating grease filler" refers to fillers used in heat dissipating grease. Heat dissipating grease is a non-curing thermal paste used to fill air pockets and gaps in electronic components, such as substrates, by applying it to them. The heat dissipating grease filler of this embodiment can improve the filler's heat resistance and inhibit moisture adsorption.
[0141] The heat dissipating grease filler of the present embodiment can be produced by kneading the composite material 10 of the first embodiment with an epoxy resin, a silicone resin, or a non-silicone acrylic resin or a ceramic resin, for example.
[0142] (Implementation 4)
[0143] Figure 4 1 is a diagram showing a schematic configuration of a resin composition 20 according to Embodiment 4. The resin composition 20 includes, for example, a filler 22 and a curable resin 24 .
[0144] The filler 22 includes the composite material 10 described in Embodiment 1. According to this embodiment, a resin composition 20 having a low dielectric loss tangent and excellent heat resistance can be provided. As the filler 22, the composite material 10 may be used alone, or other filler materials such as silica particles may be used in combination with the composite material 10.
[0145] Examples of the curable resin 24 include epoxy resins, cyanate compounds, maleimide compounds, phenolic resins, acrylic resins, polyamide resins, polyamideimide resins, thermosetting polyimide resins, and polyphenylene ether resins. The curable resin 24 may be one or a combination of two or more selected from these.
[0146] The resin composition 20 may contain other components. Examples of such other components include curing agents, flame retardants, ultraviolet absorbers, antioxidants, reaction initiators, silane coupling agents, fluorescent brighteners, photosensitizers, dyes, pigments, tackifiers, lubricants, defoamers, dispersants, leveling agents, glossing agents, antistatic agents, polymerization inhibitors, and organic solvents. As needed, one or a combination of two or more selected from these components may be used.
[0147] (Implementation 5)
[0148] The prepreg of the fifth embodiment includes Figure 4 The resin composition 20 or its semi-cured product of the fourth embodiment shown, and a fibrous substrate. The fibrous substrate is present in the matrix of the resin composition 20 or the semi-cured product. The prepreg is a composite material of the resin composition 20 and the fibrous substrate. According to this embodiment, a prepreg suitable for supporting high-frequency wiring boards can be provided.
[0149] In the present embodiment, semi-cured material represents the material that makes resin combination 20 be cured to the state midway with the degree that can further be cured.That is, semi-cured material is the material that makes the state of resin combination 20 semi-cured.For example, if resin combination 20 is heated, its viscosity slowly reduces.If continue to heat, then start to solidify afterwards, its viscosity slowly rises.In this case, as semi-cured state, the state of resin combination 20 during the moment from viscosity starting to rise to the moment of complete solidification can be listed.
[0150] As the fibrous substrate, known materials used in various laminates for electrical insulating materials can be used. Examples of the fibrous substrate include glass cloth, aramid cloth, polyester cloth, glass nonwoven fabric, aramid nonwoven fabric, polyester nonwoven fabric, pulp paper, and linter paper.
[0151] The resin composition 20 is impregnated into the fibrous base material by treatment such as dipping or coating. By heating the fibrous base material impregnated with the resin composition 20 under predetermined heating conditions, a prepreg in a pre-cured or semi-cured state according to this embodiment can be obtained.
[0152] (Implementation 6)
[0153] Figure 5 This is a cross-sectional view of a resin-coated film 30 according to Embodiment 6. The resin-coated film 30 includes a resin layer 32 containing a resin composition 20 or a semi-cured product thereof, and a support film 34. According to this embodiment, a resin-coated film 30 suitable for an insulating layer can be provided. The resin layer 32 is supported by the support film 34. Figure 5In the example shown in FIG. 3 , a support film 34 is disposed on the surface of the resin layer 32. However, another layer such as an adhesive layer may be provided between the resin layer 32 and the support film 34.
[0154] The resin layer 32 includes Figure 4 The resin composition 20 or its semi-cured product of the fourth embodiment shown may or may not contain a fibrous substrate. As the fibrous substrate, the same material as the fibrous substrate of the prepreg can be used. The resin layer 32 is cured to form an insulating layer. An example of such an insulating layer is the insulating layer of a wiring board.
[0155] Any support film used for a film with a resin can be used without limitation as the support film 34. Examples of the support film 34 include resin films such as polyester films and polyethylene terephthalate films.
[0156] (Implementation 7)
[0157] Figure 6 This is a cross-sectional view of a resin-coated metal foil 40 according to Embodiment 7. The resin-coated metal foil 40 includes a resin layer 42 containing a resin composition 20 or a semi-cured product thereof, and a metal foil 44. The resin layer 42 is supported by the metal foil 44. According to this embodiment, a resin-coated metal foil 40 suitable for electronic circuit components such as wiring boards can be provided. Figure 6 In the example shown in FIG. 4 , the metal foil 44 is disposed on the surface of the resin layer 42. However, another layer such as an adhesive layer may be provided between the resin layer 42 and the metal foil 44.
[0158] The resin layer 42 includes Figure 4 The resin composition or semi-cured product of the fourth embodiment shown may or may not contain a fibrous substrate. As the fibrous substrate, the same material as the fibrous substrate of the prepreg can be used. The resin layer 42 is cured to form an insulating layer. An example of such an insulating layer is the insulating layer of a wiring board.
[0159] As the metal foil 44, metal foil used for resin-coated metal foil and metal-clad laminate can be used without limitation. Examples of the metal foil include copper foil and aluminum foil.
[0160] (Implementation 8)
[0161] Figure 7 : is a cross-sectional view of a metal-clad laminate 50 according to an eighth embodiment. The metal-clad laminate 50 includes an insulating layer 52 and at least one metal foil 54. According to this embodiment, a metal-clad laminate 50 suitable for a wiring board can be provided. The insulating layer 52 includes Figure 4The cured product of the resin composition 20 of the embodiment 4 or the cured product of the prepreg of the embodiment 5 is shown. The metal foil 54 is arranged on the surface of the insulating layer 52. In this embodiment, the metal foil 54 is arranged on the front and back surfaces of the insulating layer 52.
[0162] The metal-clad laminate 50 is typically manufactured using the prepreg of Embodiment 5. For example, 1 to 20 prepregs are stacked to form a laminate. The metal-clad laminate 50 is obtained by placing metal foil on one or both sides of the prepreg laminate and then heating and pressurizing the laminate. Examples of the metal foil 54 include copper foil and aluminum foil.
[0163] The molding conditions for producing the metal-clad laminate 50 can be applied to the molding conditions for producing, for example, an electrically insulating laminate and a multilayer board.
[0164] (Implementation 9)
[0165] Figure 8 : is a cross-sectional view of a wiring board 60 according to the ninth embodiment. The wiring board 60 includes an insulating layer 62 and wiring 64. According to this embodiment, a wiring board 60 suitable for high frequencies can be provided. The insulating layer 62 includes Figure 4 The cured product of the resin composition 20 of the fourth embodiment or the cured product of the prepreg of the fifth embodiment is shown. The wiring 64 is supported by the insulating layer 62. Specifically, the wiring 64 is arranged on the insulating layer 62. The wiring 64 can be formed by partially removing the metal foil.
[0166] By etching and other methods Figure 7 By patterning the metal foil 54 on the surface of the metal-clad laminate 50 shown, a wiring board 60 is obtained in which wiring 64 forming a circuit is provided on the surface of the insulating layer 62. In other words, the wiring board 60 is obtained by partially removing the metal foil 54 on the surface of the metal-clad laminate 50 so as to form a circuit.
[0167] A new laminate can be formed by laminating the prepreg of Embodiment 5 on at least one surface of wiring board 60 and then heating and pressing the laminate. If the metal foil on the surface of the obtained laminate is patterned to form wiring, a multilayer wiring board can be obtained.
[0168] Example
[0169] The following examples are given to illustrate the present disclosure in detail. The examples are used to illustrate the present disclosure, not to limit it.
[0170] Example 1
[0171] Boron nitride was used as a substrate. The boron nitride was h-BN (manufactured by Denki Kagaku Co., Ltd., product number: SGP, average particle size: 18 μm). Dopamine solution (concentration: 23 mg / mL) was obtained by adding dopamine hydrochloride to a Tris-HCl solution adjusted to pH 8.5 and stirring. 4.5 g of boron nitride was added to the obtained dopamine solution. The solution temperature was set to 80°C and stirred with a magnetic stirrer for 24 hours. Then, a solid was obtained by filtration. The obtained solid was washed with water and then dried. Thus, particles of boron nitride attached with polydopamine (hereinafter referred to as polydopamine-modified boron nitride for convenience) were obtained. The attachment of polydopamine was confirmed by the surface of the boron nitride particles being colored dark brown.
[0172] Next, 2.0 g of polydopamine-modified boron nitride was added to 20 ml of deionized water. Furthermore, 0.1 g of DMAP was added as a catalyst and dissolved. Next, 2 ml of methacrylic anhydride was added as an acylating agent to form a mixed solution. The mixed solution was set to 25°C and stirred using a magnetic stirrer for 24 hours. The mixed solution was then filtered to obtain a solid. The resulting solid was washed with toluene and then dried. Thus, particles of the composite material of Example 1 were obtained.
[0173] Example 2
[0174] Particles of the composite material of Example 2 were obtained by the same method as in Example 1 except that 2 ml of acetic anhydride was used as the acylating agent instead of 2 ml of methacrylic anhydride.
[0175] Example 3
[0176] Particles of the composite material of Example 3 were obtained by the same method as in Example 1 except that 2 ml of acrylic anhydride was used as the acylating agent instead of 2 ml of methacrylic anhydride.
[0177] Example 4
[0178] Particles of the composite material of Example 4 were obtained by the same method as in Example 1 except that 20 ml of chloroform was used as the solvent instead of 20 ml of deionized water.
[0179] Comparative Example 1
[0180] As particles of Comparative Example 1, polydopamine-modified boron nitride obtained by the same method as in Example 1 was used. That is, in Comparative Example 1, polydopamine-modified boron nitride was used without being treated with an acylating agent.
[0181] The dielectric loss tangent and acylation ratio of each of the particles obtained in the above Examples and Comparative Examples were evaluated.
[0182] [Measurement of dielectric loss tangent]
[0183] The dielectric loss tangent at a frequency of 1 GHz was measured for each particle group obtained in Examples 1 to 4 and Comparative Example 1. A cavity resonator (MS46122B manufactured by AET, Inc.) was used as a measuring device.
[0184] The measurement is performed to determine whether the dielectric loss tangent is good or not. A measured value of 0.0045 or less is considered good, and a value of 0.0030 or less is considered particularly good.
[0185] [Evaluation of acylation rate]
[0186] For each particle group obtained in Examples 1 to 4 and Comparative Example 1, N2 / N1 was determined by the above-mentioned method.
[0187] The dielectric loss tangent and N2 / N1 of Examples 1 to 4 and Comparative Example 1 are shown in Table 1 together with the acylating agent and solvent used.
[0188] [Table 1]
[0189] acylating agent solvent Dielectric loss tangent <![CDATA[N2 / N1]]> Example 1 Methacrylic anhydride water 0.0024 0.386 Example 2 Acetic anhydride water 0.0027 0.425 Example 3 Acrylic anhydride water 0.0038 0.349 Example 4 Methacrylic anhydride Chloroform 0.0042 0.216 Comparative Example 1 none none 0.0072 —
[0190] Investigation
[0191] As shown in Table 1, the composite materials of Examples 1 to 4, in which at least a portion of the hydroxyl groups contained in polydopamine were acylated with an acylating agent, exhibited dielectric loss tangents of 0.0045 or less, demonstrating excellent values. The composite materials of Examples 1 to 4 satisfied the condition 0.20 ≤ N2 / N1. In Examples 1 to 3, in which water was used as the solvent, the dielectric loss tangents were 0.0040 or less, demonstrating even better values. The composite materials of Examples 1 to 3 satisfied the condition 0.35 ≤ N2 / N1.
[0192] It should be noted that this embodiment uses boron nitride as a substrate. However, it is speculated that when aluminum nitride, silicon nitride, aluminum oxide, magnesium oxide, or silicon dioxide are used instead of boron nitride, a reduction in dielectric loss tangent can also be achieved in the same manner. This is because the composite material disclosed herein achieves a reduction in dielectric loss tangent by reducing the amount of hydroxyl groups contained in polydopamine.
[0193] While the present disclosure has been appropriately and fully described above through the embodiments, it should be appreciated that those skilled in the art can easily modify and / or improve the above embodiments. Therefore, as long as the modified or improved embodiments implemented by those skilled in the art do not depart from the scope of the claims set forth in the claims, such modified or improved embodiments should be construed as falling within the scope of the claims.
[0194] Industrial applicability
[0195] The composite material disclosed herein can realize a filler with a reduced dielectric loss tangent and is therefore suitable for applications such as wiring boards of electronic devices used in large-capacity communications.
[0196] Explanation of symbols
[0197] 1.11 Base material
[0198] 2.21 Polydopamine
[0199] 3 Acylating agents
[0200] 4 Hydrophobic solvents
[0201] 5 Hydrophilic solvents
[0202] 10 Composite Materials
[0203] 20 resin composition
[0204] 22 Filling
[0205] 24 Curing resin
[0206] 30 Film with resin
[0207] 32 resin layer
[0208] 34 Support film
[0209] 40 Metal foil with resin
[0210] 42 resin layer
[0211] 44 metal foil
[0212] 50 Metal-clad laminate
[0213] 52 insulation layer
[0214] 54 metal foil
[0215] 60 wiring board
[0216] 62 insulation layer
[0217] 64 Wiring
Claims
1. A composite material comprising: Base material, and A polydopamine comprising a plurality of hydroxyl groups and at least one acyl group.
2. The composite material according to claim 1, wherein The at least one acyl group is generated by acylation of at least a part of the plurality of hydroxyl groups.
3. The composite material according to claim 1, It satisfies 0.20≤N2 / N1, N1 is the molar number of the plurality of hydroxyl groups contained in the polydopamine, N2 is the molar number of the at least one acyl group contained in the polydopamine.
4. The composite material according to claim 3, It satisfies 0.30≤N2 / N1.
5. The composite material according to claim 3 or 4, It satisfies N2 / N1≤0.
5.
6. The composite material according to claim 1, wherein The substrate includes at least one selected from the group consisting of boron nitride, aluminum nitride, silicon nitride, aluminum oxide, magnesium oxide, and silicon dioxide.
7. The composite material according to claim 6, wherein The substrate comprises boron nitride.
8. A composite material comprising: Base material, and Polydopamine comprising a functional group represented by -OCOR, R is a hydrocarbon group.
9. A filler, It comprises the composite material according to claim 1.
10. A resin composition, It contains the filler according to claim 9.
11. A prepreg, It comprises the resin composition according to claim 10 or a semi-cured product of the resin composition.
12. A film with a resin, comprising: A resin layer comprising the resin composition according to claim 10 or a semi-cured product of the resin composition, and Support film.
13. A metal foil with resin, comprising: A resin layer comprising the resin composition according to claim 10 or a semi-cured product of the resin composition, and Metal foil.
14. A metal-clad laminate comprising: An insulating layer comprising a cured product of the resin composition according to claim 10 or a cured product of the prepreg according to claim 11, and Metal foil.
15. A wiring board comprising: An insulating layer comprising a cured product of the resin composition according to claim 10 or a cured product of the prepreg according to claim 11, and wiring.
16. A method for manufacturing a composite material, comprising the following steps: contacting a material containing polydopamine containing a plurality of hydroxyl groups with an acylating agent, and acylate at least a portion of the plurality of hydroxyl groups, The material includes a substrate and the polydopamine attached to the surface of the substrate.
17. The method for producing a composite material according to claim 16, wherein: The acylation is carried out in a hydrophilic solvent.
18. The method for producing a composite material according to claim 17, wherein: The hydrophilic solvent includes water.
19. The method for producing a composite material according to claim 16, wherein: The acylating agent comprises an acid anhydride.
20. The method for producing a composite material according to claim 19, wherein: The acid anhydride includes at least one selected from the group consisting of methacrylic anhydride, acrylic anhydride, acetic anhydride, and benzoic anhydride.
Citation Information
Patent Citations
Hexagonal boron nitride powder
JP2018043899A